TEACHERS' EFFORTS IN DEALING WITH STUDENTS WHO EXPERIENCE BOREDOM DURING LEARNING IN ELEMENTARY SCHOOL - Farinda Khasanah; Henry Aditia Rigianti (Renjana Pendidikan Dasar, 2023)
A teacher must have efforts that can deal with learning boredom in students, because teachers have a great responsibility in guiding, teaching, and developing students. In the face of student boredom, teachers need to have thoroughness, patience, and skills in managing the classroom. Teachers must be able to identify signs of boredom, respond quickly, and take appropriate steps to restore learners' interest and motivation in learning. Through learning that is engaging, interactive, and tailored to the individual needs of learners, boredom can be reduced, learning motivation can be increased, and learners can achieve better results in the learning process. This study aims to describe (1) the factors that cause student boredom during learning in elementary school, (2) discuss specific approaches, such as the use of technology, differentiation approaches, and collaboration with students, (3) the efforts of elementary school teachers in dealing with students who experience boredom. This research was conducted using qualitative descriptive methods. This research was conducted through in-depth interviews with several experienced teachers.